Major surface melting over the Ross Ice Shelf part I: Foehn effect. (4th June 2021) - Zou, Xun; Bromwich, David H.; Montenegro, Alvaro; Wang, Sheng‐Hung; Bai, Lesheng
Abstract: West Antarctica (WA), especially the Ross Ice Shelf (RIS), has experienced more frequent surface melting during the austral summer recently. The future is likely to see enhanced surface melting that will jeopardize the stability of ice shelves and cause ice loss. We investigate four major melt cases over the RIS via Polar Weather Research and Forecasting (WRF) simulations (4 km resolution) driven by European Centre for Medium‐Range Weather Forecasts (ECMWF) Reanalysis 5th Generation (ERA5) reanalysis data and Moderate Resolution Imaging Spectroradiometer (MODIS) observed albedo. Direct warm air advection, recurring foehn effect, and cloud/upper warm air introduced radiative warming are the three major regional causes of surface melting over WA. In this paper, Part I, the first two factors are identified and quantified. The second paper, Part II, discusses the impact of clouds and summarizes all three factors from a surface energy balance perspective. With a high‐pressure ridge located westward towards the Sulzberger Ice Shelf (77° S, 148° W) and a low‐pressure center located between 165° and 180° W, warm marine air from the Ross Sea is advected towards the coastal RIS and leads to surface melting. When the high‐pressure ridge is located farther east towards Marie Byrd Land (120–150° W), the foehn effect can cause a 2–4°C increase in surface temperature on the leeside of the mountains. For three of four melt cases, more than 40% of the melting period experiences foehn warming. Isentropic drawdown is usually the dominant foehn mechanism and contributes up to a 14°C temperature increase, especially when strong low‐level blocking occurs on the upwind side. The thermodynamic mechanism can be important depending on the strength of moisture uptake and condensation on the windward side. Meanwhile, sensible heat flux contributes less to foehn warming, but still plays an important role in the melting. The prediction of future stability of the RIS should include foehn warming as a major driver. Abstract : This study investigates two regional drivers for surface melting over the Ross Ice Shelf (RIS) of Antarctica, recurring foehn effect and direct warm air advection, based on four extensive melt cases via Polar WRF outputs. The foehn effect can contribute ∼4°C temperature increase, while the impact of direct warm air advection rarely impacts farther inland and rarely leads to strong melting. Thus, prediction of the future stability of the RIS should include foehn effect as a major factor.